Chemical composition, in vitro antioxidant and antibacterial activities of Centaurea resupinata subsp. dufourii (dostál) greuter. Issue 22 (8th December 2020) - Bouzghaia, Badra; Moussa, Mohammed Tahar Ben; Goudjil, Rima; Harkat, Hassina; Pale, Patrick
Abstract: The current study focuses on the chemical composition, and evaluation of antioxidant and antibacterial activity of the aerial parts of Centaurea resupinata subsp. dufourii . Using different chromatographic methods nine compounds 1–9 were isolated. The structural identification of isolated compounds was achieved using several spectroscopic methods NMR techniques ( 1 H NMR, 13 C NMR, COSY, HSQC, HMBC) and mass spectroscopy (ESI-MS) and by comparison with literature data. The structures of these compounds were identified as nicotiflorin (1), apigetrin (2), chrysoeriol (3), apigenin (4), chrysin (5), daucosterol (6), β-sitosterol (7), taraxastrerol (8) and lupeol (9). The antibacterial and antioxidant activities of ethyl acetate and n -butanol extracts have been evaluated. The antioxidant activity was assessed in vitro using DPPH radical scavenging method, which showed that ethyl acetate extract possessed an interesting antioxidant potential (IC50  = 36.263 ± 0.005 μg/mL). Graphical Abstract: